Ecophysiological traits and activity patterns of coleopterans from Atacama Desert provide clues to the functional responses of small ectotherms to climate change. (March 2018) - Tirado, Carlos; Trujillo, Daniel; Pizarro-Araya, Jaime; Alfaro, Fermín M.; González, Sylvana; Carretero, Miguel A.
Abstract: There is an increasing contribution of ecophysiology in community ecology and climate change contexts. As such, functional patterns under extreme water and temperature restrictions in deserts can provide inference of the responses of small ectotherms to climate change. However disentangling the interactive effects between both factors requires experimental evidence. Here we took advantage of a flowering desert episode promoting a population bloom in Gyriosomus (Coleoptera: Tenebrionidae) beetles from Atacama Desert to test this interactive hypothesis. By systematically sampling two sympatric Gyriosomus species, we analyzed the differences in activity, body temperature and water loss rate. Body size regardless the species or sex was responsible for the observed behavioral and ecophysiological patterns. Large coleopterans (females > males, G. kingi  >  G. planicollis ) lost less water and were active at higher temperatures making their bimodal diel activity less marked. Beyond the confirmation of the crucial role of water availability and inactivity in arid ecosystems, these results suggest that functional responses of small ectotherms to climate change will be size-dependent while advocate for integrating hydric and thermal data to better understand this transition. Highlights: Testing integrative hypothesis of ecophysiology and activity with coleopterans from Atacama desert. Size is the major factor accounting for the differences between species and sexes. Beetles prevent overheating and extreme water loss by decreasing activity. Such effect is higher in small animals regardless species and sex. Repercussions for climate change responses of small ectotherms.